Southeast Asia and the English school of international relations a region-theory dialogue - Quayle, Linda (Palgrave studies in international relations series, 2013)
This book examines the interface between the theoretical framework known as the English School and the international and transnational politics of Southeast Asia. The region-theory dialogue it proposes signals productive ways forward for the theory.